Agreement between heart rate variability - derived vs. ventilatory and lactate thresholds A systematic review with meta-analyses - Tanner, V.; Millet, G. P.; Bourdillon, N. (Research Square, 2024)
Background This systematic review with meta-analyses aims to assess the overall validity of the first and second heart rate variability - derived threshold (HRVT1 and HRVT2, respectively) by computing global effect sizes for agreement and correlation between HRVTs and reference - lactate and ventilatory (LT-VTs) - thresholds. Furthermore, this review aims to assess the impact of subjects` characteristics, HRV methods, and study protocols on the agreement and correlation between LT-VTs and HRVTs.